2017
DOI: 10.1177/0272989x17707198
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Continuous “Spinners” to Communicate Risk

Abstract: As patients become more involved in their medical care, they must consider the specific probabilities of both positive and negative outcomes associated with different treatments. Patients who are low in numeracy may be at a disadvantage when making these decisions. This study examines the use of a “spinner” to present probabilistic information compared to a numerical format and icon array. Subjects were asked to imagine they suffered from chronic back pain. Two equally effective medications, each with a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Others have also demonstrated less effect of visual aids among subjects with higher levels of education and/or numeracy. (8, 16, 18) In this study, college graduates may have had pre-existing perceptions of these drugs (e.g., due to higher prior knowledge) and therefore may have been less impacted by additional information. Alternatively, they may have been more confident in their own knowledge and/or beliefs, and may have overlooked the additional information describing risks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Others have also demonstrated less effect of visual aids among subjects with higher levels of education and/or numeracy. (8, 16, 18) In this study, college graduates may have had pre-existing perceptions of these drugs (e.g., due to higher prior knowledge) and therefore may have been less impacted by additional information. Alternatively, they may have been more confident in their own knowledge and/or beliefs, and may have overlooked the additional information describing risks.…”
Section: Discussionmentioning
confidence: 92%
“…This finding suggests that the conceptual illustrations may have had an impact on participants’ mental representations of risk associated with the graphic representation, but not the numbers only format. Numerous studies have compared graphic representations to other risk presentation formats (18, 2026); however, the effect of combining formats is not well understood. Future studies using cognitive interviews, think aloud protocols, or hypothesis-driven experiments are needed to better understand the differential impact of the graphic representation and/or conceptual illustrations for rare and very rare events.…”
Section: Discussionmentioning
confidence: 99%
“…24−28 A recent paper by Eyler et al proposed using a continuous "spinner" to communicate risk based on studies in children demonstrating improved understanding of probabilities when shown continuous versus discrete patterns. 29 The study found that both the spinner and icon array increased subjects' risk knowledge, although the effect was not modified by numeracy. 29 Our aim was to examine how individuals understand uncertainty as it relates to the probability of medication risks and benefits, and to specifically analyze their understanding of epistemic and aleatory uncertainty.…”
Section: Introductionmentioning
confidence: 89%
“…29 The study found that both the spinner and icon array increased subjects' risk knowledge, although the effect was not modified by numeracy. 29 Our aim was to examine how individuals understand uncertainty as it relates to the probability of medication risks and benefits, and to specifically analyze their understanding of epistemic and aleatory uncertainty. Additionally, given the conflicting evidence regarding the effectiveness of visual aids in increasing understanding of uncertainty, we aimed to study how people think about both the icon array and spinner.…”
Section: Introductionmentioning
confidence: 89%
“…20 This has led to various recommendations about appropriate design and approaches used in patient decision aids. 11,17,[21][22][23][24][25][26][27] Visual representation of risk information has been shown to increase the accuracy of risk comprehension and improve decision making for patients. 11,17 Previous studies have identified conflicting evidence regarding the influence of icon arrays on improving risk comprehension (Minshall et al, unpublished data, 2018).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%